(3QSGdI aj GdELeGYs - (3GdYGedj, GdTgjO GdKGfj, Rjf GdOjf Hf Ydj Hf CMeO, J (B966(3g` (B1559(3es ((3fhQhR GdWGQejs)
(3ChdgG (B:s
(3ChdgG(B: (3aGFOI JTJed Ydi GdJfHjg Ydi eSGFd GOYi ajgG GdTjN GdELeGY eY Cfg faSg NGda aj Mce eG GOYi GdELeGY ajgs
(3BNQgG (B:s
(3BNQgG(B: (3bGd aj a(B: (3fYe jMJLG HGdELeGY hGdCNHGQ(B. (3hbGd aj W(B: (3dG JLH(B. (3hbGd aj a(B: (3dG jONd GdCHGA hGdChdGO aj GdYbd eMJLG HGdELeGY(B. (3hbGd aj jg(B: (3jONdhf ajg(B. (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B3: 64s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs